Custos de produção, produtividade e impacto ambiental: um estudo comparativo nas cultivares orizícolas IRGA 417, sistema Clearfield IRGA 422 CL e Arize 1003 - Carlesso, Stele Bicca da Silva (2010)
The evaluation of the costs involved in a production process becomes an increasingly essential tool for making decisions. In rice production there are several factors that may affect, directly or indirectly, the productivity and profitability. Besides the natural factors, like soil and climate, the choice of cultivar, the infra-structure and management system of the field, the logistic, and others, will be directly associated with the expected return of the investment. Besides these factors, is unthinkable to accomplish any activity without worry about an environmentally safe technology and production. The general objective of this dissertation is: search and compare the costs of production, productivity and environmental impacts between the systems of rice cultivars: Conventional, Clearfield and hybrid . Thus, the study started from the needs of a rice producer in the central region of Rio Grande do Sul State (Brazil) to know the production costs, productivity and environmental impacts associated with three types of rice cultivar systems most commonly used today, the Conventional Rice IRGA 417, IRGA 422 CL Clearfield System and the hybrid Arize 1003. Through unstructured interviews with the producer and the agronomist, observation "in loco" and documentary research lead to the production costs to be obtained for the goal of comparison in the diverse steps needed to the rice field production to facilitate data analysis and achieve the proposed goals. The results obtained allowed the producer the correct verification of which cultivar showed the highest efficiency in technical, economical end environmental subjects.